Molecular footprint and pathways of DOM biotransformation in the Yangtze River - Guangrui Yang; Farong Chen; Songchol Kang; Jiaming Chen; Chu Zhao; Lize Meng; Xinyi Zhang; Jiayue Lu; Shuaidong Li; Zihao Bian; Jian Zhou; Qihao Jiang; et al. (Water Research, 2026)

Low-carbon preparation of blast furnace burden from iron ore concentrates via cold-bonding process: New insights into the effect of concentrate type - Xiaolong Wang; Zhiyun Ji; Xiaohui Fan; Min Gan; Shaochun Li; Shengxuan Fan; Zengqing Sun; Jiaming Lv; Yanqing Du; Jiasheng Li; Ying Yu (Minerals Engineering, 2026)

4-Pentenoic acid exhibits broad-spectrum antibacterial activity against foodborne pathogens by disrupting bacterial membrane integrity and inhibiting efflux pump systems - Jiaming Mu; Jie Li; Fushuang Duan; Rui Wen; Xuepeng Cai; Qingling Meng; Jun Qiao; Zhongmei Ma (International Journal of Food Microbiology, 2026)

Highly dispersed Ni-Mo encapsulated in hollow mesoporous ZSM-5 as an efficient catalyst for tetralin conversion to light aromatics - Mengdi Wang; Limin Zhang; Haoqing Zhang; Jiaming Wu; Keyan Li; Xinwen Guo (Fuel, 2026)

Deconstructing soil detachment: integrated assessment of soil properties, root characteristics, and hydraulics under diverse land uses on the Chinese loess plateau - JianFang Wang; JiaMing Li; GuoBin Liu; WeiWei Ma; Bing Wang (CATENA, 2026)

Impacts of carbon source type on metabolic pathways and microbial synergy in the simultaneous anammox and endogenous denitrification process - Wenlong Liu; Yuyan Zhang; Chenhao Yue; Jiaming Wang; Jun Li; Huijie Lu; Shilong He; Yongzhen Peng (Bioresource Technology, 2026)

Integrative genetic analysis reveals shared genetic architecture underlying coronary artery disease, CT-Defined coronary atherosclerosis, and cardiometabolic risk factors - Yao Zhao; Yingying Xie; Didi Wen; Jin Zhang; Ziliang Xu; Zhibin Wu; Jiaming Li; Yuanqiang Zhu; Minwen Zheng (Functional & Integrative Genomics, 2026)

Origin of Early Cretaceous magmatism and its linkage with Cu–Fe–Au skarn mineralization in the Tonglushan ore field, eastern China: Evidence from whole-rock, zircon, and apatite geochemistry - Ming Zhang; Xiangzhou Li; Yanyan Zhao; Shichao Shang; Jiaming Zhou; Wan Huang; Yiheng Liu; Ziqing Yan; Xiaoyang Liu; Jun Tan (Lithos, 2026)

Constant-voltage triboelectric nanogenerator coupled with an intermittent speed-up mechanism and bionic jellyfish blades for low-speed water flow energy harvesting - Chenxi Li; Yongle Zhou; Fupu Xie; Jiaming Zhang; Yi Li; Hongwei Wang; Kaisheng Li; Zihao Li; Siyuan Liu; Tianyu Li (Chemical Engineering Journal, 2026)

Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Sustainable urban transitions in resource-based cities: How transition willingness translates into external green technology acquisition - Jiachuan Liu; Peiyuan Zhang; Jiaming Li; Shuo Lu; Wenzhong Zhang (Sustainable Production and Consumption, 2026)

De-localization of global cities: How advanced producer services exacerbate regional spatial inequality? - Jiaming Li; Jiachuan Liu (Land Use Policy, 2026)

Machine learning prediction and interpretability of sewage sludge pyrolysis gas yield and composition - Yi Xiao; Jingyi Li; Qigui Niu; Tianxue Yang; Jiaming Zhao; Xiaowei Wang; Dongyang Li (Journal of Environmental Chemical Engineering, 2026)

Time-resolved volatile profiles and molecular-species lipid remodeling during lipase treatment of anhydrous milk fat - Anqi Chen; Qingyun Xu; Jiaming Li; Yanxi Chen; Qiance Shen; Guocheng Du; Jianghua Li; Jian Chen (Food Research International, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Study on the influence of different cold shock methods on the mechanical properties and rockburst proneness of high-temperature monzogranite - Jiaming Li; Xinyu Liu; Shuguang Zhang; Shibin Tang; Xiang Huang; Wenbo Liu (Engineering Geology, 2026)

Thermal-buffering cellulose aerogels with competitive hydrogen bonding: Dual-enthalpy synergy for efficient solar desalination - Mengqi Lu; Shuyue Zhang; Jiangquan Yang; Wei Li; Shuangfei Wang; Shouxin Liu; Jiaming Sun; Shuangxi Nie (Chemical Engineering Journal, 2026)

Carbide-induced high dispersion and electronic regulation of Pt species toward stable propane dehydrogenation - Xiaonan Wang; Jiaming Ma; Jun Li; Haoyu Yan; Zhikai Yang; Bo Jiang; Xiao Zhang (Chemical Engineering Journal, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Strain-specific fermentation reshapes aroma-active volatiles and antioxidant-related properties of soy protein isolate-based plant milk - Hanhan Shi; Jiaming Li; Tanxu Tang; Tianzhi Qu; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2026)

Nanoconfined humic acid-supported nZVI enhances imidacloprid remediation without compromising soil microbiome or exacerbating ARG health risks - Na Li; Jiaming Yi; Lin Zhu; Du Chen; Meizhen Wang; Dan Huang (Environmental Research, 2026)

Air plasma constructing multi-defects in NiFe metal-organic frameworks for enhanced electrocatalysis - Jiaming Zhao; Yilin Li; Xuchen Miao; Yuanbo Wang; Xingyun Li; Yubao Liu; Zhiliang Liu; Guoling Li (Chemical Engineering Journal, 2026)

Multiscale solvation-electronic regulation strategy toward stable Zn anode - Jiaqi Li; Yushan Ma; Yicheng Wang; Shaoyu Zhang; Jiaming Li; Nan Li; Junyi Han; Hedong Gu; Zhanhong Yang; Xiaolei Wang (Chemical Engineering Journal, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Machine learning-assisted smartphone fluorescence sensing for ultrasensitive and point-of-care testing of acid phosphatase - Fusheng Zhong; Jiaming Zhang; Huaxi Ruan; Tonglong Yang; Jinbo Cao; Liangliang Peng; Jinhui Liu; Qingqing Deng; Li Wang (Analytica Chimica Acta, 2026)

High-accuracy estimation of global site-level soil heterotrophic respiration through Geo-XGBoost integration with expanded datasets and remote sensing - Jie Liu; Ni Huang; Luying Zhu; Jiaming Chang; Yuting Shi; Zheng Niu; Dewen Cai; Li Wang (Agricultural and Forest Meteorology, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

Abscisic acid promotes watercore dissipation by accelerating sorbitol decomposition through the MdNAC25-MdSDH8 module in apple fruit - Yali Li; Hao Wei; Qian Ma; Jiaming Li; Zuanhong Xu; Yamei Ren; Xiaolin Ren; Yuduan Ding (Postharvest Biology and Technology, 2026)

Revealing the antioxidant potential of Artemisia integrifolia L.: Integrated discovery of bioactive compounds via UHPLC-DPPH and activation of the Nrf2/HO-1 signaling pathway - Huimin Li; Qian Gao; Yijin Wu; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Inner-body governing mechanisms for shear-driven gas leakage flow over a ventilated supercavity - Wang Zou; Jiaming Wang; Liuxuan Li; Chongguang Wang; Hanyu Gan; Hanxu Qiu (Ocean Engineering, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Humic acid-mediated activation of antimony colloid during soil redox cycles: Mechanisms and environmental implications - Xiongkai Zheng; Jiaming Xu; Haiming Cai; Qiming Mo; Yihao Li; Qixian Fu; Lijuan Zeng; Yongyang Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Garnet microtextures and geochemistry of the Tonglushan Cu–Fe–Au skarn deposit (Edong district): Constraints on fluid evolution and skarn mineralization - Ming Zhang; Xiangzhou Li; Ziqing Yan; Shichao Shang; Wan Huang; Yanyan Zhao; Jiaming Zhou; Xiaoyang Liu; Jingui Huang; Jun Tan (Journal of Geochemical Exploration, 2026)

Auxiliary fermentation with Pediococcus acidilactici C1 reshapes flavor formation in sufu: An integrated metagenomic, flavoromic and non-targeted metabolomic deciphering - Chen Chen; Jiaming Li; Feng Wang; Mei Cheng; Tao Sheng; Zahoor Ahmed; Jingwei Hu; Yibin Zhou (Food Chemistry, 2026)

Defined co-fermentation of Kluyveromyces marxianus and lactic acid bacteria enhances bioactivity and aroma formation in black tea kombucha - Aiping Yao; Jiaming Li; Yuanyuan Zhao; Tianzhi Qu; Yan Geng; Lingxi Zhou; Anqi Chen; Jian Chen (Food Bioscience, 2026)

The extract of Cirsium setosum exerts antimicrobial activities on largemouth bass infected by Aeromonas veronii via regulating inflammatory and antioxidant responses - Yuhuan Qiu; Chutong Zhang; Dekun Tang; Dasen Li; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Maternal Stress During Pregnancy Induces Higher Anxiety-Like Behavior in Male Mice Offspring Under Acute Stress by Upregulating CRF/CRFR1 and Driving Time-Specific Activation of the MHb-IPN Circuit - Yujie Wang; Jiajia Zhao; Yueyang Wang; Zhixin Du; Li Wang; Zibo Ma; Siyang Sun; Xinyang Qu; Xiaohan Geng; Jiaming Yan; Liping Yang; Junlin Hou (Neuroscience Bulletin, 2026)

Polyphase of uranium mineralization in granite-related deposits: Insights from the geochronology and geochemistry of pitchblende and coffinite in the Xiwang uranium deposit, South China - Bin Liu; Weifeng Chen; Haidong Li; Jiaming Qi; Liang Qiu; Hongfei Ling (Applied Geochemistry, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Gibberellic acid modulated ethylene, ascorbate-glutathione cycle, and fatty acid metabolism to attenuate the browning of watercore apple fruit: Insights from transcriptomic evidence - Yali Li; Hao Wei; Yunya Zhao; Jiaming Li; Zuanhong Xu; Changhao Song; Yamei Ren; Xiaolin Ren; Yuduan Ding (Postharvest Biology and Technology, 2026)

Study on the synergistic melting combustion characteristics of municipal solid waste incineration fly ash and circulating fluidized bed gasification fly ash - Wei Li; Jiaming Chen; Shaobo Yang; Qiangqiang Ren (Fuel, 2026)

A novel approach to distinguish the respective contributions of galvanic effect and reactive oxygen species on sulfide mineral dissolution: Insights from stibnite and pyrite - Xiaoqian Li; Jingxuan Qiu; Xingjie Wang; Jiaming Du; Deng Liu; Chun Li; Hongmei Wang; Liyuan Ma (Chemical Geology, 2026)

Identifying the environmental drivers of the distribution of carbon isotopes in global inland waters - Jiahui Shi; Lixiao Ni; Jiaming Liu; Yushen Ma; Yiping Li; Carlo Gualtieri (Water Research, 2026)

Fully coupled numerical model of moored structures-mooring line-ice ridge interaction - Jiaming Chen; Shengjie Rui; Sen Han; Shifeng Ding; Jie Tan; Li Zhou (Ocean Engineering, 2026)

Rapid joule heating synthesis of oxygen-vacancy-rich high-entropy oxide as a high-performance electrocatalyst for OER - Li Wu; Ziheng Bian; Jiaming Zhao; Yaqi Yang; Lili Guan; Yarong Huang; Xiwen Song (Journal of Environmental Chemical Engineering, 2026)

A novel multifunctional bacterial consortium synergistically promotes rhizoremediation of dibutyl phthalate and cucumber growth: Insights from multi-omics analyses - Jiaming Xu; Yan Li; Haoyan Han; Yi Wu; Yue Tao; Yuexuan Ma; Zhao Jiang; Ying Zhang (Journal of Environmental Sciences, 2026)

The formation of gypsum ridges in the endorheic Qaidam Basin and implications for irregular polygonal ridges on Mars - Zikang Li; Jiaming Zhu; Ziyu Niu; Bo Wu; Yiliang Li (Icarus, 2026)

Paeoniae Radix Rubra extract inhibits largemouth bass ranavirus (LMBV) replication by suppressing inflammatory response and oxidative stress - Yang Liu; Dasen Li; Wenyan Liu; Chutong Zhang; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

Spatial mismatch and inequality between ecological pressure and economic benefits embodied in agricultural trade - Kaige Lei; Jiaming Zhang; Yan Li; Xinhui Feng; Jiayu Yang; Li Hou; Jianguo Liu (Environmental Impact Assessment Review, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Multi-omics analysis revealed promoting mechanism of gut derived cellulose-degrading bacteria from Tenebrio molitor on bioconversion of lignocellulosic waste - Xinrui Mao; Wenbiao Jin; Jiaming Li (Bioresource Technology Reports, 2026)

Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

GIS-based Geotourism Route Design in Changbaishan Global Geopark - Junbo Zhao; Jinxin He; Jian Yi; Xiangjin Ran; Jiaming Li (Geoheritage, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

MDSN-Net: A multi-domain spectral nexus network for underwater accurate fish counting - Jiaming Xin; Tongtong Gu; Zhengmeng Wu; Yiying Wang; Dashe Li; Huanhai Yang (Computers and Electronics in Agriculture, 2026)

How built environments shape leisure jogging styles: Nonlinear and interactive effects across objective and subjective dimensions - Wei Yang; Mengjia Yin; Longyang Huang; Jiaming Sun; Caixuan Guo; Xin Fan; Jingjing Li (Journal of Transport Geography, 2026)

Structured wave-transparent metamaterials for simultaneous broadband electromagnetic and acoustic absorption - Tongtong Zhang; Qingxuan Liang; Yubing Duan; Xin Yan; Aoqi Ren; Jiaming Feng; Dichen Li (Chemical Engineering Journal, 2026)

Gaδ+-H active sites-driven reverse water gas shift reaction with high CO selectivity - Zhenzhong Tao; Huaixiang Li; Dedong He; Zijun Huang; Jun Liang; Jiaming Dong; Xiaohua Cao; Yongming Luo (Chemical Engineering Journal, 2026)

Development of an indirect ELISA and an immunochromatographic test method for early detection of Haemonchus contortus infection in sheep - Xueqiu Chen; Lingyun Mou; Manqin Deng; Jingju Zhang; Jiaming Yu; Jianfang Li; Hongli Zhang; Guangxu Ma; Yi Yang; Aifang Du (Veterinary Parasitology, 2026)

Identification of conserved vaccine targets in Mycoplasma bovis through integrated pan-genome and reverse vaccinology approaches with in vivo immunogenicity and safety evaluation - Jiaming Mu; Zhongmei Ma; Jie Li; Xuepeng Cai; Qingling Meng; Jun Qiao (The Veterinary Journal, 2026)

Optimization design research of vibration control parameters for Submerged Floating Tunnel based on GA-AIF-PSO algorithm - Jiaming Xie; Jianyun Chen; Ning Su; Jing Li; Qiang Xu (Ocean Engineering, 2026)

Aerodynamic and wake characteristic analysis of a dual-rotor wind turbine under surge motion based on modified actuator line model - Mengshang Zhao; Kai Wang; Siqi Chen; Jiaming Liu; Yuan Li (Ocean Engineering, 2026)

Investigation of CO2 absorption and desorption performance and mechanism of aqueous [TETAH][Im] in a PTFE hollow fiber membrane contactor - Chunyun Zhou; Yanbin Yun; Chang Li; Jia Liu; Jiaming Mao; Wenjuan Yang; Haiyan Huang; Guoqiang Zhuang; Meng Li (Journal of Environmental Chemical Engineering, 2026)

A comparative study of maturity, gas emissions, and microbial communities during kitchen waste, food waste, and food waste digestate composting - Xia Gao; Jiani Wang; Jiaming Li; Kaishu Luo; Xingshuai Yang; Guoxue Li; Yilin Kong; Jing Yuan (Journal of Environmental Chemical Engineering, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Accumulation of volatiles under salt crusts in the highly evaporative Qaidam basin: Implications for salt crust fluid processes on Mars - Jiaming Zhu; Bo Wu; Zikang Li; Yiliang Li (Earth and Planetary Science Letters, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Impacts of anthropogenic activities on habitat fragmentation and their spatial heterogeneity in the Himalayas - Jiaming Li; Jiachuan Liu (Journal of Geographical Sciences, 2026)

Impact of Sedimentary Environmental Evolution on Organic Matter Enrichment in Upper Paleozoic Marine-Continental Transitional Shales in the Shenfu Block, Eastern Ordos Basin, China: Evidence from Geochemistry - Yanchao Zhang; Xiangdong Yin; Shu Jiang; Litao Ma; Jiaming Li (Journal of Earth Science, 2026)

Efficacy and Safety of OnabotulinumtoxinA for the Treatment of Masseter Muscle Prominence in a Chinese Population: 6-Month Results From a Phase 3, Randomized, Placebo-Controlled Study - Jiaming Sun; Yuejun Li; Tianjiao Yang; Jia Chang (Toxicon, 2026)

Unintended environmental risks of regional PV expansion: A climate-adjusted lifecycle analysis for sustainable deployment - Jiawen Liu; Liangzhong Li; Yangyang Wu; Jiaming Wang; Futian Ren; Peng Wang; Lei Huang (Journal of Environmental Management, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Anthropogenic sustained increase in near bottom suspended particulate matter concentration of the deep marginal sea - Zhuangcai Tian; Xiujun Guo; Jiaming Xiang; Tong Li; Jinran Wu (Environmental Research, 2026)

Research on bearing capacity of laser welding reinforcement of spherical joint region of spatial grid structure - Caibao Liu; Xiongyan Li; Wei Wang; Suduo Xue; Jiaming Yang (Engineering Structures, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Urban Pluvial Flood Maximum Water Depth Prediction Using a Transformer-CNN Hybrid Deep Learning Model with Data Augmentation - Ziqi Liu; Dejun Zhu; Jiaming Luo; Danxun Li (Water Resources Management, 2026)

Adaptive Classification Model Based on Dynamic Variations in Microseismic Signal Characteristics - Jinglan Zhang; Jiaming Li; Beichang Tang; Shuguang Zhang; Shibin Tang (Rock Mechanics and Rock Engineering, 2026)

Different geographical patterns and assembly mechanisms of phytoplankton and benthic diatoms: a case study in a cold temperate wetland cluster - Yongxu Duan; Zhengxun Li; Jiaming Liu; Zheng Hou; Henglin Xiao; Yan Liu; Yawen Fan; Xinxin Lu (Hydrobiologia, 2026)

Prediction of Heterogeneous Shale Lithology in the Kaijiang–Liangping Trough Based on Dream Optimization Algorithm and Support Vector Machine - Lexin Yuan; Zhiming Xu; Haofei Sun; Jungang Lu; Luchuan Zhang; Xiangdong Yin; Jiaming Li (Mathematical Geosciences, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Anti-inflammatory metabolites from the leaves of Ohwia caudata - Qianqian Zhang; Ping Zhang; Yijin Wu; Huimin Li; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Post-mortem analysis of degradation behavior in catalyst layers of proton exchange membrane fuel cell under near-water boiling temperature - Daijun Yang; Bo Zhou; Yirui Lu; Jiaming Lou; Bing Li; Pingwen Ming (Fuel, 2026)

Pipeline Systems in Floating Offshore Production Systems: Hydrodynamics, Corrosion, Design and Maintenance - Jin Yan; Yining Zhang; Zehan Chen; Pengji Li; Yuting Li; Zeyu Cao; Jiaming Wu; Kefan Yang; Dapeng Zhang (Journal of Marine Science and Engineering, 2026)
Floating offshore production systems play a critical role in offshore resource development, where the structural integrity and operational safety of risers, umbilical cables, and mooring cables are of paramount importance. Focusing on the failure risks of these key components under harsh marine environments, this paper systematically reviews the coupled mechanisms of wave-induced loading, electrochemical corrosion, and material fatigue. Unlike traditional reviews on offshore pipelines and cables, this study not only examines the mechanical performance of deepwater pipelines and cables along with representative research cases but also discusses corrosion mechanisms in marine environments and corresponding repair and mitigation strategies. In addition, recent advances in machine learning-based digital twin frameworks and real-time monitoring technologies are reviewed, with an analysis of representative application cases. The findings indicate that interdisciplinary material innovations combined with data-driven predictive models are essential for addressing maintenance challenges under extreme ocean conditions. Furthermore, this review identifies existing research gaps in data fusion for monitoring technologies and outlines clear directions for the intelligent operation and maintenance of future deep-sea infrastructure.

Br radicals generated via bromate-free photoactivation may promote degradation of emerging contaminants in highly saline waters - Min Zhao; Jiaming Gan; Yingdong Li; Mingbao Feng; Hamid Mohammed Al-Gabr; Xin Yu; Lei Wang (Water Research, 2026)

Monitoring contaminant removal during in situ chemical oxidation using cross-borehole resistivity tomography and hydrogeology - Teng Xia; Jiaming Zhang; Ruijue Zhao; Miao Li; Shupeng Li; Lili Guo; Deqiang Mao (Journal of Hydrology, 2026)

Metformin drives the antibiotic resistome in activated sludge by reshaping microbial communities and promoting horizontal gene transfer - Jiaming Yi; Zhengtao Li; Xuezhu Han; Jingpeng Li; Haotian Liu; Lin Zhu; Meizhen Wang (Journal of Hazardous Materials, 2026)

Emerging evidence of nighttime mercury oxidation driven by nitrate radical-activated heterogeneous halogen chemistry - Yan Wang; Zhenya Duan; Yi Tang; Shuxiao Wang; Zhijian Li; Qin Wang; Jiaming Fu; Qingru Wu (Journal of Hazardous Materials, 2026)

Post-mortem analysis of the degradation behavior of the fuel cell gas diffusion layer under near to water boiling point conditions - Yirui Lu; Daijun Yang; Jiaming Lou; Bo Zhou; Xiangyang Zhou; Xiangmin Pan; Bing Li; Pingwen Ming (Chemical Engineering Journal, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

Extreme precipitation amplified the cumulative effects of DOM availability on organic-sourced DIC in the Yangtze River - Chu Zhao; Guangrui Yang; Lize Meng; Heran Chen; Shuaidong Li; Farong Chen; Zihao Bian; Jiaming Chen; Jian Zhou; Qihao Jiang; Tao Huang; Hao Yang; et al. (Water Research, 2025)

Targeting argH to attenuate Aeromonas dhakensis virulence: A metabolic checkpoint for biofilm formation and stress adaptation - Xueqian Wang; Chenlu Yang; Xuesong Li; Wei Feng; Jianguo Zhao; Yukun Wu; Shuai Ye; Meng Zhao; Hanzeng Li; Jiaming Ju; Guiying Guo; Lixia Fan; et al. (Veterinary Microbiology, 2025)

Spatial-interaction-context and temporal-attention U-Net model for spatio-temporal prediction of Sea Surface Temperature field - Jiaming Ma; Jun Song; Junru Guo; Yanzhao Fu; Yu Cai; Yuan Zhang; Jie Tian; Ming Li (Regional Studies in Marine Science, 2025)

Potential strategies of natural products in the treatment of atherosclerosis: Focusing on modulating macrophage polarization - Wenjie Zhao; Peng Sun; Jiaming Huan; Lei Zhang; Shijing Peng; Tong Jiang; Linghui Kong; Xinghao Zhu; Wenqing Yang; Dongmei Qi; Yunlun Li (PharmaNutrition, 2025)

Advancing kombucha fermentation: Microbial interactions, functional metabolites, and innovative optimization strategies - Anqi Chen; Jiaming Li; Aiping Yao; Guocheng Du; Jianghua Li; Jian Chen (Food Chemistry, 2025)

Convenient DNA extraction integrated with dual RPA-LFA technology for simultaneous detection of Salmonella and Listeria monocytogenes - Jiaming Huang; Jing Sun; Xinyi Pang; Xiangfei Li; Xiaomei Bie; Yingjian Lu (Food Bioscience, 2025)

CRISPR/Cas12b-mediated one-tube live cell assay facilitates Salmonella typhimurium detection in poultry meat - Yongjin Dai; Jiaming Huang; Moran Zhang; Xinyi Pang; Xiangfei Li; Jing Sun; Yingjian Lu (Food Bioscience, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

A differentiated study of the impact of command and market-based environmental regulation on corporate R&D investments —take China's coal power industry chain as an example - Jiaming Gao; Li Zhang (Energy Policy, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Phenytoin quaternary ammonium salt is a novel wound treatment drug with both pro-healing and antibacterial effects - Yuchen Li; Jiaming Cui; Peihui Zhou; Bixuan Cao; Li Zhao; Weize Kong; Xueheng Sun; Ya Fang; Jinwu Wang; Mingzhi Song; Li Wang (Chemical Engineering Journal, 2025)

Injectable nanocomposite hydrogel with antibacterial/osteogenic dual functions for synergistic repair of infectious bone defects in hyperlipidemia microenvironment - Yongkai Wang; Yunhan Sun; Jiaming Song; Dongchen Fa; Yuting Qu; Jiayi Li; Xiao Fu; Li Ma (Chemical Engineering Journal, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Thermostatic nucleic acid amplification technology in foodborne pathogen detection: opportunities and challenges - Moran Zhang; Jiaming Huang; Yongjin Dai; Shanshan Jin; Qianqian Jia; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (Critical Reviews in Food Science and Nutrition, 2025)

Gastrodin inhibits hexokinase-2 mediated glycolysis to rescue rotenone-damaged PC12 cells - Min Chen; Jiaming Tian; Buyun Jia; Meng Wang; Anqi Han; Jiming Zhu; Shasha Tian; Xiaoming Gao; Baikun Li; Qinglin Li; Shanshan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

MKAIS: A Hybrid Mamba–KAN Neural Network for Vessel Trajectory Prediction - Caiquan Xiong; Jiaming Li; Yuzhe Zhuang; Xinyun Wu; Mao Luo; Qi Wang (Journal of Marine Science and Engineering, 2025)
Vessel trajectory prediction (VTP) plays a critical role in maritime safety and intelligent navigation. Existing methods struggle to simultaneously capture long-term dependencies and nonlinear dynamic patterns in vessel movements. To address this challenge, we propose MKAIS, a novel trajectory prediction model that integrates the selective state space modeling capability of Mamba with the strong nonlinear representation power of Kolmogorov–Arnold Networks (KAN). Specifically, we design a feature-separated embedding strategy for AIS inputs (longitude, latitude, speed over ground, course over ground), followed by an MKAN module that jointly models global temporal dependencies and nonlinear dynamics. Experiments on the public ct_dma dataset demonstrate that MKAIS outperforms state-of-the-art baselines (LSTM, Transformer, TrAISformer, Mamba), achieving up to 16.65% improvement in the Haversine distance over 3 h prediction horizons. These results highlight the effectiveness and robustness of MKAIS for both short-term and long-term vessel trajectory prediction.

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

Research on the dynamic properties of rubber-recycled brick-coarse aggregate concrete through pore structure evolution - Shucheng Yuan; Jiayu Zeng; Jiaming Mai; Siwei Du; Yanjindong Yi; Kunpeng Li; Wei Liang (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

How to restrict informal recycling of photovoltaic modules: Research on closed-loop supply chain decision-making of photovoltaic modules under different recycling subsidy policies - Jiaming Gao; Li Zhang (Journal of Cleaner Production, 2025)

Energy analysis and microfracture characteristics of granite under dynamic modes I and II loading based on image processing techniques - Zida Liu; Zong-Xian Zhang; Quanqi Zhu; Peng Xiao; Jiaming Yang; Diyuan Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Hybrid fabrication of perfusable stiffness-flexible integrated scaffold mimicking hierarchical tubular bone - Yifan Zhang; Zhipeng Li; Bingkun Bao; Jingyi Ju; Wenbin Jiang; Linyong Zhu; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Direct electrospinning of super fatigue resistant and fire-retardant aerogels for thermal insulation - Lingyun Wu; Jiaming Li; Yunfang Liu; Manxi Zhou; Dan Xue; Gang Bai; Aosong Zhou; Xiaoping Yang; Gang Sui (Chemical Engineering Journal, 2025)

Integrated multi-omics reveals mechanistic impact of gut microbiota inhibition on lignocellulose biodegradation in Tenebrio molitor - Xinrui Mao; Jiaming Li; Wenbiao Jin; Wei Han (Bioresource Technology, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Synthesis of ultrafine boehmite from waste coal fly ash by integrating sol-gel process with sodium aluminate decomposition and hydrothermal treatment - Shuwei Lan; Zhaowen Wang; Qianhan Zhao; Zhibo Liu; Jiaming Li (Journal of Environmental Chemical Engineering, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Mechanochemical treatment and valorization of hazardous fluorine from aluminum electrolyte in spent carbon anodes - Zhibo Liu; Zhenkun He; Bingqing Liu; Wenju Tao; Jiaxin Yang; Jiaming Li; Xianwei Hu; Zhaowen Wang (Journal of Environmental Chemical Engineering, 2025)

Exploring the functional diversity of wild Saccharomyces cerevisiae strains for breadmaking applications - Chenwei Pan; Jiaming Li; Tianzhi Qu; Hui Liu; Weiming Xiao; Bo Chen; Anqi Chen; Jian Chen (Food Bioscience, 2025)

Improving storage stability of dairy emulsions via xanthan gum and carboxymethyl cellulose synergy - Qingyun Xu; Jiaming Li; Fanjun Meng; Yanfang Sun; Xuexian Du; Yingle Wu; Jianguo Yan; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2025)

Parallel algorithm of watershed delineation by considering the topological relationship into information organisation - Fei Zhao; Liyang Xiong; Hongen Wang; Lanhua Luo; Jiaming Na; Sijin Li; Guoan Tang (Environmental Modelling & Software, 2025)

Hydrophilic and lipophilic diblock polymer-based co-delivery nanoplatform for impossible mission: Resistance management toward insecticides via Nrf2-sMaf pathway - Jiajia Zhao; Zeng Wang; Jiaming Yin; Ying Wei; Mingshan Li; Jialin Gou; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Insight shift from laboratory to industrialization for tail gas-based ethanol production - Jiaming Gu; Danfeng Wang; Qun Shen; Li Shang; Guofei Shen; Nannan Sun; Shuhuan Tong; Wei Chao; Yangyang Guo; Wei Wei (Chemical Engineering Journal, 2025)

The links between Na/K ratios in eolian sands and mean annual precipitation in the deserts of arid region, northern China - Jiaqi Wang; Shipei Dong; Zhuolun Li; Jiaming Qu; Yuhan Kuai; Dianjia Tan; Jie Luo (CATENA, 2025)

Corrigendum to “Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms” [Catena 254 (2025) 108882] - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

An efficient fish counting method with adaptive global perception and multi-scale feature perception - Yiying Wang; Dashe Li; Jiaming Xin (Aquacultural Engineering, 2025)

Numerical Simulation of an Icebreaker Ramming the Ice Ridge - Wenbo Dong; Jiaming Chen; Yufei Zhang; Shisong Wei; Guangwei He; Fang Li (Journal of Marine Science and Engineering, 2025)
During polar navigation, icebreakers frequently encounter ice ridges, which can significantly reduce navigation efficiency and even pose threats to structural safety. Therefore, studying the ramming of ice ridges by the icebreaker is of great importance. In this study, the ice ridge is decoupled into the consolidated layer and the keel for modeling. The consolidated layer is simplified as layered ice, and an innovative hybrid empirical–numerical method is used to determine the icebreaking loads. For the keel, a failure model is developed using the Mohr–Coulomb criterion in combination with the effective stress principle, accounting for shear failure in porous media and incorporating both cohesion and internal friction angle. The ship is restricted to surge motion only. A comparative analysis with the model test results was conducted to assess the accuracy of the method, with the predicted ice resistance showing deviation of 9.85% in the consolidated ice area and 10.48% in the keel area. Ablation studies were conducted to investigate the effects of different ice ridge shapes, varying retreat distances, and different ship drafts on the performance of ramming the ice ridge. The proposed method can quickly and accurately calculate ice ridge loads and predict their motion responses, providing a suitable tool for on-site rapid navigability assessment and for the design of icebreakers.

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Enhancing vessel trajectory prediction with bi-state space and squeeze excitation attention - Caiquan Xiong; Jiaming Li; Xinyun Wu; Donghua Liu; Qi Wang; Rong Gao; Jinjia Ruan (Ocean Engineering, 2025)

Dynamic interplay between core functional microbial succession and flavor metabolite formation in naturally fermented sufu: A multi-omics perspective - Chen Chen; Jiaming Li; Zahoor Ahmed; Changyue Deng; Feng Wang; Jingwei Hu; Yibin Zhou (Food Bioscience, 2025)

Neuroprotective effects of Yangming-Kaixin-Yizhi formula in Alzheimer’s disease: dual regulation of PI3K/Akt and p38 MAPK signaling via network pharmacology and experimental approaches - Jing Lei; Jiaming Li; Wei Wu; Rui Xiong; Yao Liu; Yong Tang (Metabolic Brain Disease, 2025)

Towards efficient in situ gas thermal desorption remediation assisted with cross-borehole resistivity tomography - Teng Xia; Jiaming Zhang; Miao Li; Shupeng Li; Lili Guo; Peng Liu; Dixiang Wang; Deqiang Mao (Water Research, 2025)

Highly selective aerobic oxidation of polystyrene to benzoic acid catalyzed by nitrogen dioxide - Yunkai Yu; Yue Zhu; Jiaming Liu; Minghao Zhang; Jing Li; Shicheng Zhang; Qingqing Mei (Science Bulletin, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Study on membrane electrolysis for the removal of Fe from the leachate of coal fly ash - Shuwei Lan; Youjian Yang; Zhaowen Wang; Yanchen Zheng; Jiaming Li; Qianhan Zhao; Tingting Liu (Journal of Environmental Chemical Engineering, 2025)

Dynamic optimization of cooling temperature setpoints in multiple thermal zones of office buildings in connection with D3QN - Ben Jiang; Jiaming Wang; Yu Li; Peng Wang; Yacine Rezgui; Chengyu Zhang; Menglin Ding; Liuyang Shangguan; Tianyi Zhao (Energy and Buildings, 2025)

Emission Characteristics and Absorption Removal of Ultra-high Concentration NOx in an Arc-Heated Wind Tunnel - Zhiliang Xue; Jie Yuan; Jiaming Shao; Pei Li; Yonggang Zhou; Tao Zhu; Zhihua Wang (International Journal of Environmental Research, 2025)

Better inversion of rice nitrogen nutrition index at early panicle initiation stage using spectral features, texture features, and wavelet features based on UAV multispectral imagery - Ziwei Li; Yuliang Zhang; Jiaming Lu; Yuan Wang; Can Zhao; Weiling Wang; Jianjun Wang; Hongcheng Zhang; Zhongyang Huo (European Journal of Agronomy, 2025)

Insight of multi-polarization effect by constructing high-entropy spinel ferrite/perovskite @ amorphous carbon for enhancing electromagnetic wave absorption - Xinyang Liu; Zhekai Zhang; Fengyu Wu; Fenyang Tian; Jie Sheng; Menggang Li; Jiaming Li; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

Efficient and anti-interference plastic classification method suitable for one-shot learning based on laser induced breakdown spectroscopy - Zhiying Xu; Xingyu Zhao; Xinying Peng; Kai Wang; Kedong Wang; Nan Zhao; Jiaming Li; Qingmao Zhang; Xueqing Yan; Kun Zhu (Chemosphere, 2025)

Study on rockburst control of deep-buried tunnel by combining advanced stress release borehole and hydraulic fracturing - Jiaming Li; Shibin Tang; Tianjiao Li; Shuguang Zhang; Liexian Tang; Kang Sun (Tunnelling and Underground Space Technology, 2025)

FeS/rGO modified cathode for enhanced electrochemical activity and TCE degradation in PS-MFC system - Chunji Li; Guanlin Chen; Jiaming Guo; Yinghao Shi; Jikun Li; Jingchun Tang (Journal of Environmental Chemical Engineering, 2025)

Ultrasensitive nanoenzymes-based lateral flow immunoassay platform for accurate detection of folic acid in human serum - Jinbo Cao; Tiemei Li; Xianglin Liao; Jiaming Zhang; Xixiang Yang; Huiqi Yan; Boyang Sun; Yanfei Li; Jiaxiang Huang; Yao Wang; Xiaogang Hu; Li Wang (Chemical Engineering Journal, 2025)

Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Sensor fault diagnosis and calibration based on voting mechanism for online application using virtual in-situ calibration and time series prediction - Jiteng Li; Jiaming Wang; Peng Wang; Sungmin Yoon; Yu Li; Yacine Rezgui; Yuxin Li; Tianyi Zhao (Building and Environment, 2025)

Evaluation of Geosites in Changbaishan Global Geopark based on Fuzzy AHP and TOPSIS - Jiaming Li; Jinxin He; Peng Lu; Xiangjin Ran; Jian Yi (Geoheritage, 2025)

Phytoextraction of Soil Cadmium by Vetiveria zizanioides Dead Shoots - Wenwen Li; Ning Liu; Xiaoling Tan; Ruoyao Shen; Jiaming Yu; Jie Li; Khateeb Hussain; Shiyong Yang (Bulletin of Environmental Contamination and Toxicology, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Multitask intelligent early warning of rockbursts based on classification-regression cascaded network model - Jiaming Li; Shibin Tang; Jinglan Zhang; Beichang Tang; Shuguang Zhang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Oxidation mechanisms of ammonia and ethanol mixed fuel by using the ReaxFF-MD simulation - Chongchong She; Chunchen Xu; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

Characterization and risk-quantification of antibiotic resistome in grain-based and non-grain cropping soils - Jingpeng Li; Lin Zhu; Xiaodi Li; Xuezhu Han; Jiaming Yi; Ying Wu; Meizhen Wang (Environmental Pollution, 2025)

Near-white light-emitting copper nanoclusters/starch composites for multiplexing imaging and multichannel enhancement of latent fingerprints - Zhibo Gao; Chuanjun Yuan; Ming Li; Zhize Xu; Meng Wang; Jiaming Lyu; Shiqiang Sun; Fenghe Liu; Peiliang Han (Chemical Engineering Journal, 2025)

Enhanced carbon dioxide capture via amphiphobic PVDF membrane modification for membrane contactors: Overcoming wettability challenges - Chang Li; Yanbin Yun; Fengguang Huang; Jiaming Mao; Jia Liu; Wenjuan Yang; Chunyun Zhou; Meng Li (Chemical Engineering Journal, 2025)

Efficient lithium recycling from waste aluminum electrolytes through an environmentally friendly process - Jiaxin Yang; Wenju Tao; Jiaming Li; Jingui He; Zhaowen Wang (Chemical Engineering Journal, 2025)

Highly stable anode-free solid-state sodium batteries enabled by electrostatic shielding and nitrogenated interphase - Wuliang Feng; Caixia Li; Peiyao Wang; Jiaming Hu; Xuan Yu; Ying Zhang; Xingbao Zhu; Dengsong Zhang; Yongyao Xia; Yufeng Zhao (Chemical Engineering Journal, 2025)

One-dimensional LATP nanofiber reinforced PEO solid composite electrolyte for all-solid-state lithium-ion batteries with excellent cycling performance - Yudi Guo; Erqing Zhao; Weifang Su; Zhe Liu; Jiaming Li (Chemical Engineering Journal, 2025)

Anhydrous deep eutectic solvents-based biphasic absorbents for efficient CO2 capture: Unravelling the critical role of hydrogen bond-mediated electron transfer - Jiaming Mao; Yunqian Ma; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Chunyun Zhou; Hongwei Xie; Yanbin Yun (Chemical Engineering Journal, 2025)

Low-dose exposure to microplastics retards meiotic maturation via HDAC3 insufficiency - Qi Zhao; Ming Zong; Entong Song; Hongye Linghu; Xuanwen Li; Baicui Wang; Songling Xiao; Wanchun Guan; Jianzhong Su; Jiaming Zhang; Jingzhang Ji; Qingran Kong (Science China Life Sciences, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

Mechanism of rice bran removal at individual grain and population levels in abrasive rice mill - Ze Sun; Xinlei Wang; Anqi Li; Jiaming Fei; Wenyu Feng; Dan Zhao; Yanlong Han; Fuguo Jia; Hao Li; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2025)

ADAM17 promotes colorectal cancer migration and invasion by regulating the TGF-β/Smad signaling pathway - Jiaming Li; Tingjin Zheng; Yingzhi Xu; Mengcha Tian; Liangpan Shi; Jintu Chen; Tian Li; Zhishan Zhang (Tissue and Cell, 2025)

Classification-enhanced LSTM model for predicting river water levels - Jiaming Luo; Dejun Zhu; Danxun Li (Journal of Hydrology, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Dual redox-centered p(thiophene-TPA) conjugated polymers for high-performance flexible electrochromic supercapacitors - Xu Cheng; Chunhui Du; Jiaming Li; Yuqiao Zhang; Wenyuan Xu; Jianming Zhang; Hui Shi; Ge Zhang; Long Zhang (Chemical Engineering Journal, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Chronic chlorpyrifos exposure induces oxidative stress, neurological damage, and hepatopancreas enrichment in Chinese mitten crab (Eriocheir sinensis) - Yuanyuan Tan; Jiaming Dong; Luyao Wang; Weining Li; Jie Bao; Hongbo Jiang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

VCU-Net: a vascular convolutional network with feature splicing for cerebrovascular image segmentation - Mengxin Li; Fan Lv; Jiaming Chen; Kunyan Zheng; Jingwen Zhao (Medical & Biological Engineering & Computing, 2025)

Evolution of in-situ thermal-enhanced oxidative remediation monitored by induced polarization tomography - Teng Xia; Jiaming Zhang; Miao Li; Damien Jougnot; Kai Yang; Shupeng Li; Deqiang Mao (Journal of Hydrology, 2025)

Development of dual polymerase spiral reaction for detection of Listeria monocytogenes and Staphylococcus aureus simultaneously - Moran Zhang; Hongzhou Chen; Jiaming Huang; Yongjin Dai; Yujuan Liu; Xiyao Zhou; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (International Journal of Food Microbiology, 2025)

Iron-containing tailings catalyst modified by Mn for SCR of NO with NH3 at low temperature: Study of carrier treatment and calcination temperature - Limin Hou; Jiaming Li; Haobo Li; Wenfei Wu (Fuel, 2025)

A functional fluorine (F)-containing oxidiser of nano-networked NH4CuF3 to improve the combustion efficiency of Al powder - Xiandie Zhang; Haozhe Li; Xuxu Cui; Weiduo Fei; Xinwen Ma; Jiaming Liu; Pingyun Li; Xiaode Guo; Xiang Zhou (Fuel, 2025)

Tracking Cr(VI) removal with spectral induced polarization under ZVI and AC synergetic remediation - Xinmin Ma; Jiaming Zhang; Chen Chao; Shiliang Liu; Khalil Ur Rahman; Shupeng Li; Lili Guo; Deqiang Mao (Environmental Research, 2025)

High performance two photon polymerization resin designed for sub-micron precision and millimeter scale structure manufacturing - Jiaming Hu; Yang Gao; Lukun Wu; Bowen Zheng; Ning Li; Kai Du; Jing Li; Shuai Zhang (Chemical Engineering Journal, 2025)

Intergenerational differences and influencing factors of farmers’ terrace abandonment behavior: Based on a questionnaire survey of 2382 rural households in China - Jiaming Wen; Shilong Luo; Hualin Xie; Xiubin Li (Journal of Geographical Sciences, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Insights into the combustion mechanisms of turpentine oil based on ReaxFF molecular dynamics simulations - Chongchong She; Tiancheng Zhang; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Cement-MgO synergetic stabilized earth-straw mix: From material performance to building simulation - Jiaming Cui; Junjie Li; Yi Du; Guillaume Habert (Energy and Buildings, 2025)

Haversian bone mimicking scaffold with built-in vasculature for bone tissue engineering - Jian Liu; Zhen You; Xinmei Li; Boyang Zhang; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Mapping QTLs for stigma exsertion-related traits in two sets of CSSL populations of Oryza sativa cultivars using RSTEP-LRT method - Chunyu Jing; Mei Hai; Jiaming Shen; Xinru Li; Mengyuan Zhang; Changmin Hu; Qing Xu; Jianhua Jiang; Xiaojing Dang (Euphytica, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

Insights into the effects of environmental factors on phytoplankton and microzooplankton at a basin scale: diversity, assembly mechanisms, and co-occurrence networks - Yanjun Shen; Xinxin Zhou; Jiaming Zhang; Qinghua Li; Yufeng Zhang; Qing Zuo (Frontiers in Marine Science, 2024)
Mastering the characteristics of planktonic microbial communities under the influence of basin-scale environmental factors can provide scientific basis to develop more targeted protection and restoration measures. Here, an environmental DNA metabarcoding technology was applied to investigate the phytoplankton and microzooplankton simultaneously along the whole basin of Jialing River, one of the most important rivers in Southwest China with large scale altitude gradient and water temperature discrepancy. Along the river-way from upper to lower reach, an upward trend in richness of both phytoplankton and microzooplankton was observed with significant positive and negative correlations to water temperature and altitude (Spearman correlation, p < 0.05), respectively. Significant variations in their compositions along the river were also uncovered with Chrysophyta and Foraminifera was potential keystones recognized by the co-occurrence network analysis. Additionally, exponential distance-decay of similarities were detected for both phytoplankton and microzooplankton, which were stronger for phytoplankton. Based on the results of variation partitioning analysis and null model, variations in phytoplankton communities were more governed by environmental selection than those in microzooplankton. Furthermore, the co-occurrence network showed a declining trend in the complexity and stability from the upper to lower reaches. These findings could serve to establish a basis for the investigation of phytoplankton and microzooplankton communities in rivers with multiple artificial modifications.

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Investigation of rice debranning mechanism based on tribological behaviour between rice grains - Jiaming Fei; Ze Sun; Dan Zhao; Anqi Li; Fuguo Jia; Yanlong Han; Hao Li; Shouyu Ji; Zhuozhuang Li; Wenyu Feng (Biosystems Engineering, 2024)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

SCARF: A new algorithm for continuous prediction of biomass dynamics using machine learning and Landsat time series - Yingchun Fu; Runhao Li; Zhe Zhu; Yufei Xue; Hu Ding; Xinyu Wang; Jiaming Na; Weijie Xia (Remote Sensing of Environment, 2024)

Efficient depolymerization of lactic acid oligomers into lactide with low racemization - Jiaming Yu; Ting Li; Qifeng Wei; Xiulian Ren (Journal of Environmental Chemical Engineering, 2024)

Can wood harvest followed by forest regrowth enhance carbon sequestration of the forest sector in China? - Mengyu Wang; Chao Yue; Junhao He; Pengyi Zhang; Mengyang Xu; Yu Li; Jiaming Wang; Lele Wang; Can Xu (Global and Planetary Change, 2024)

Rapid and accurate AuNPs-sodium deoxycholate-propidium monoazide-qPCR technique for simultaneous detection of viable Listeria monocytogenes and Salmonella - Jiaming Huang; Xinyi Pang; Xiangfei Li; Xiaomei Bie; Jing Sun; Yingjian Lu (Food Control, 2024)

SbSeI for high-efficient photocatalytic degradation of multiple pollutants - Kang Li; Yue Gao; Zhongxin Dong; Huibo Zhang; Xudong Fan; Lei Xu; Jie Huang; Feng Teng; Haibo Fan; Jiaming Song; Chunmei Zhang; Xuexia He; et al. (Environmental Research, 2024)

Environmentally friendly recycling of energy storage functional materials from hazardous waste lithium-containing aluminum electrolytes - Jiaxin Yang; Wenju Tao; Jiaming Li; Lingyu Kong; Shaohua Wu; Jingui He; Zhaoshun Liu; Yu Sun; Chao Fan; Zhaowen Wang (Chemical Engineering Journal, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Spatial Patterns and Drivers of Intelligent Manufacturing from a ‘Global-local’ Perspective: A Study of China’s Industrial Robotics - Fengjiao Li; Hong Zhang; Lili Jiang; Jiaming Liu (Chinese Geographical Science, 2024)

Environmental DNA (eDNA) reveals the effects of cascade dam development on the distribution patterns of aquatic biodiversity in mountain rivers - Yanjun Shen; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Ruli Cheng (Frontiers in Marine Science, 2024)
The rich and special biodiversity in mountain rivers is experiencing a continuous decline due to the influence of climate change and anthropogenic factors. To explore the alterations in the distribution of aquatic biodiversity in mountain rivers in the context of cascade dam development, the environmental DNA (eDNA) metabarcoding technique was used to examine the aquatic biodiversity of the Wujiang River, a representative mountain river with an 11-stage cascade dam. In this study, a comprehensive analysis of aquatic organisms in the Wujiang River mainstem was conducted, and 17 phyla and 38 classes were detected in the 36 water samples. The most abundant group is the benthic organisms, and the least abundant group is the amphibians. The results of the diversity analysis showed a clear longitudinal distribution pattern of aquatic organisms along the altitudinal gradient, with higher richness of aquatic organism communities the further to the lower reaches. Meanwhile, RDA analysis revealed that altitude, dissolved oxygen, reservoir length, and reservoir construction time were the key environmental factors influencing the distribution of aquatic organisms in the Wujiang River mainstem. The findings of this research also showed the applicability of the eDNA method in detecting aquatic biodiversity.

Near-infrared responsive photocatalysts for environmental remediation and energy conversion: A review - Jiaming Li; Yuan Li; Dmitry Selishchev; Gaoke Zhang (Chemosphere, 2024)

Fleet availability analysis and prediction for shared e-scooters: An energy perspective - Jiahui Zhao; Jiaming Wu; Sunney Fotedar; Zhibin Li; Pan Liu (Transportation Research Part D: Transport and Environment, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

A strategy for treatment of low-grade ore: Efficient separation and purification of iron - Shishun Dong; Ting Li; Jiaming Yu; Qifeng Wei; Xiulian Ren (Process Safety and Environmental Protection, 2024)

Water-induced surface ordering facilitating the microcutting of ductile metals - Jiong Zhang; Xiaopeng Wang; Lu Ma; Shibo Xi; Jiaming Zhan; Ruipeng Li; Yonghua Du; Junmin Xue; Hao Wang (Journal of Cleaner Production, 2024)

Co-governance of open pit mines across China based on exposure risk assessment of particulate matter - Shuo Lu; Wenzhong Zhang; Peng Zeng; Jiaming Li (Journal of Cleaner Production, 2024)

Construction of La1−xSrxNiO3/g-C3N4 type-Z heterojunctions with enhanced visible-light photocatalytic degradation of organic pollutants - Pengke Yu; Jiaxing Guo; Liang Guo; Yaqin Deng; Juntao Tan; Qunang Xu; Qingmao Zhang; Jiaming Li (Environmental Research, 2024)

Enhanced photocatalytic CO2 reduction to CH4 on oxygen vacancy-rich NiCo2O4 with surface pits: Synthesis, DFT calculations, and mechanistic insights - Jiaming Li; Yuan Li; Minsu Han; Yusuke Yamauchi; Gaoke Zhang (Chemical Engineering Journal, 2024)

Regulatory mechanisms of miR171d–SCL6 module in the rooting process of Acer rubrum L. - Huiju Li; Jiayu Yu; Jiaming Qin; Hewen Zhao; Kezhong Zhang; Wei Ge (Planta, 2024)

The dynamics of some exact solutions to a ( 3 + 1 ) -dimensional sine-Gordon equation - Jiaming Guo; Maohua Li (Wave Motion, 2024)

Transport processes of dissolved and particulate nitrogen and phosphorus over urban road surface during rainfall runoff - Yang Xiao; Chi Zhang; Taotao Zhang; Bin Luan; Jiaming Liu; Qiang Zhou; Chentao Li; Haoke Cheng (Science of The Total Environment, 2024)

Online sorting of surface defective walnuts based on deep learning - Jingwei Wang; Xiaopeng Bai; Daochun Xu; Wenbin Li; Siyuan Tong; Jiaming Zhang (Journal of Food Engineering, 2024)

A novel process for recovering LNCM battery cathode material using cryolite-based electrolyte through selective dissolution - Acid leaching - Coprecipitation - Jiaming Li; Youjian Yang; Jiaxin Yang; Shuwei Lan; Zhaowen Wang (Journal of Cleaner Production, 2024)

A novel sunflower-like nanocarrier based on dual milk-derived proteins for improved bio-accessibility, stability and antioxidant activity of anthocyanin - Shuangshuang Wang; Yi Ding; Liqing Xu; Jiaming Li; Minghui Zhang; Qisheng Hu; Haiyan Wang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Hydrocolloids, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

The involvement of tumor necrosis factor receptor-associated factor 6 in regulating immune response by NF-κB at pre-molt stage of Chinese mitten crab (Eriocheir sinensis) - Jialin Li; Yuhan Ma; Zihao Wu; Jiaming Li; Fengchi Wang; Zhichao Yang; Yuting Xi; Dazuo Yang; Yusheng Jiang; Qilin Yi; Shu Huang (Fish & Shellfish Immunology, 2024)

Recent research progress of MOFs-based heterostructures for photocatalytic hydrogen evolution - Jiaming Li; Jia Jia; Deping Wang; Hongjun Dong; Mingshan Zhu (Chemical Engineering Journal, 2024)

The New Roles of traf6 Gene Involved in the Development of Zebrafish Liver and Gonads - Hongyan Xu; Wenzhuo Ban; Jiaming Tian; Jianfei Xu; Zhimin Tan; Sendong Li; Kaili Chen; Mi Ou; Kaibin Li (Marine Biotechnology, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Water and fertilizer decision model for synergistic optimization of yield, quality and efficiency of cherry tomato based on combination evaluation - Rui Li; Jiaming Bai; Dayong Li; Xinru Ren; Daiwei He; Rongcheng Du; Ziqi Feng; Zhi Zhang (Computers and Electronics in Agriculture, 2024)

A new paradigm for construction safety management in China: Introducing knowledge graph and accident database into the early-stage of BIM - Wangxin Li; Ping Wu; Jiaming Huang; Yidong Xu (Journal of Cleaner Production, 2024)

Preparation of salicylic acid nano-protectant with dual synergistic mechanism: High direct fungicidal activity and plant defence toward cotton Verticillium wilt - Jiaming Yin; Jiajia Zhao; Zeng Wang; Fan Xue; Qi Wang; Huiming Guo; Hongmei Cheng; Jie Li; Jie Shen; Meizhen Yin; Xiaofeng Su; Shuo Yan (Chemical Engineering Journal, 2024)

Facet-dependent activation of oxalic acid over hematite nanocrystals under the irradiation of visible light for efficient degradation of pollutants - Zhixiong Yang; Yuan Li; Xiaotian Wang; Jiaming Li; Jiquan Wang; Gaoke Zhang (Journal of Environmental Sciences, 2024)

Boosting charge transfer promotes photocatalytic peroxymonosulfate activation of S-doped CuBi2O4 nanorods for ciprofloxacin degradation: Key role of Ov–Cu–S and mechanism insight - Xianzhong Bu; Jiaming Li; Jin Wang; Yuan Li; Gaoke Zhang (Chemical Engineering Journal, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Effects of DeSUMOylated Spastin on AMPA Receptor Surface Delivery and Synaptic Function Are Enhanced by Phosphorylating at Ser210 - Wenbin Zhang; Jiaqi Zhang; Zhongqi Zhang; Shuhan Cha; Jiong Li; Li Chen; Jiaming Wu; Jijun Teng; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2024)

Genome-wide identification and expression analysis of the SOD gene family under biotic and abiotic stresses in sweet orange - Xulin Li; Ke Wen; Tuo Yin; Chaoying Chen; Ling Zhu; Xiuyao Yang; Yinqiang Zi; Ke Zhao; Jiaming Zhang; Hanyao Zhang (Plant Biotechnology Reports, 2024)

DNA Methylation is Involved in Sex Determination in Spinach - Keli Jia; Jiaming Duan; Guangqian Cheng; Heng Li; Shufen Li; Miao Hu (Biochemical Genetics, 2024)

Informer-Based Model for Long-Term Ship Trajectory Prediction - Caiquan Xiong; Hao Shi; Jiaming Li; Xinyun Wu; Rong Gao (Journal of Marine Science and Engineering, 2024)
Ship trajectory prediction is a complex time series forecasting problem that necessitates models capable of accurately capturing both long-term trends and short-term fluctuations in vessel movements. While existing deep learning models excel in short-term predictions, they struggle with long-sequence time series forecasting (LSTF) due to difficulties in capturing long-term dependencies, resulting in significant prediction errors. This paper proposes the Informer-TP method, leveraging Automatic Identification System (AIS) data and based on the Informer model, to enhance the ability to capture long-term dependencies, thereby improving the accuracy of long-term ship trajectory predictions. Firstly, AIS data are preprocessed and divided into trajectory segments. Secondly, the time series is separated from the trajectory data in each segment and input into the model. The Informer model is utilized to improve long-term ship trajectory prediction ability, and the output mechanism is adjusted to enable predictions for each segment. Finally, the proposed model’s effectiveness is validated through comparisons with baseline models, and the influence of various sequence lengths Ltoken on the Informer-TP model is explored. Experimental results show that compared with other models, the proposed model exhibits the lowest Mean Squared Error, Mean Absolute Error, and Haversine distance in long-term forecasting, demonstrating that the model can effectively capture long-term dependencies in the trajectories, thereby improving the accuracy of long-term vessel trajectory predictions. This provides an effective and feasible method for ensuring ship navigation safety and advancing intelligent shipping.

Towards sustainable development in resource-based cities: Assessing the effects of extraregional technology and investment on the low-carbon transition - Shuo Lu; Jiaming Li; Wenzhong Zhang; Fan Xiao (Journal of Environmental Management, 2024)

Experimental and theoretical investigation of an ionic liquid-based biphasic solvent for post-combustion CO2 Capture: Breaking through the “Trade-off” effect of viscosity and loading - Jiaming Mao; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Yanbin Yun; Guicheng Liu; Meng Li; Manxiang Wang (Chemical Engineering Journal, 2024)

Stepwise extraction of lithium and potassium and recovery of fluoride from aluminum electrolyte wastes through calcification roasting–two-stage leaching - Shaohua Wu; Wenju Tao; Hui Ge; Jiaxin Yang; Jiaming Li; Jingui He; Youjian Yang; Zhaowen Wang (Environmental Science and Pollution Research, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

A study on ice resistance prediction based on deep learning data generation method - Qianyang Sun; Jiaming Chen; Li Zhou; Shifeng Ding; Sen Han (Ocean Engineering, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Development of CaCl2·6H2O-mannitol/SiO2 shape-stabilized composite phase change material for the radiant cooling panel system - Jiaming Zhang; Haiwen Li; Yanliang Du; Tao Xu; Ting Zou; Shen Wei; Dongqiao Zhang (Energy and Buildings, 2024)

Applicability and limitation of compost maturity evaluation indicators: A review - Yilin Kong; Jing Zhang; Xuanshuo Zhang; Xia Gao; Jie Yin; Guoying Wang; Jiaming Li; Guoxue Li; Zhongliang Cui; Jing Yuan (Chemical Engineering Journal, 2024)

Responses of physiological, microbiome and lipid metabolism to lignocellulose wastes in gut of yellow mealworm (Tenebrio molitor) - Xinrui Mao; Jiaming Li; Enqing Meng; Wenbiao Jin; Wei Han (Bioresource Technology, 2024)

Rab18 maintains homeostasis of subcutaneous adipose tissue to prevent obesity-induced metabolic disorders - Jiaming Liu; Liangkui Li; Dijin Xu; Yuqi Li; Tao Chen; Yeyang Liu; Yuqian Bao; Yan Wang; Longyan Yang; Peng Li; Li Xu (Science China Life Sciences, 2024)

Synthesis and antiviral property of polysulfate-grafted maleimide-based enediynes - Zhuoyu Li; Zhe Ding; Haonan Cheng; Xiaofan Zhang; Houjun Zhang; Gary Wong; Yun Ding; Jiaming Lan; Aiguo Hu (Medicinal Chemistry Research, 2024)

Live chicken body fat measurement technology based on bio-electrical impedance - Jiaming Zuo; Jinping Liang; Shangshang Cheng; Yuelin Deng; Zhenhui Li; Qinghua Nie; Dexiang Zhang; Xiquan Zhang; Zhen Li; Hongmei Li (Computers and Electronics in Agriculture, 2024)

Effect of temperature on the occurrence of Metschnikowia bicuspidata disease in Eriocheir sinensis - Hongbo Jiang; Gangnan Cao; Jie Bao; Chengcheng Feng; Xiaodong Li; Yuanyuan Tan; Jiaming Dong; Qijun Chen (Aquaculture, 2024)

PcPME63 is involved in fruit softening during post-cold storage process of European pear (Pyrus communis L.) - Beibei Cao; Rongxiang Zhu; Manyi Sun; Bobo Song; Jun Wu; Jiaming Li (Postharvest Biology and Technology, 2024)

Transporters and phytohormones analysis reveals differential regulation of ryegrass (Lolium perenne L.) in response to cadmium and arsenic stresses - Wenwen Li; Jie Li; Khateeb Hussain; Kaihao Peng; Jiaming Yu; Miaoqing Xu; Shiyong Yang (Journal of Hazardous Materials, 2024)

Biochar reduces gaseous emissions during poultry manure composting: Evidence from the evolution of associated functional genes - Ruijing Dang; Yu Cai; Jiaming Li; Yilin Kong; Tao Jiang; Jiali Chang; Sheng Yao; Jing Yuan; Guoxue Li; Guoying Wang (Journal of Cleaner Production, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

Establishment of a gill cell line from yellowfin seabream ( Acanthopagrus latus ) for studying Amyloodinium ocellatum infection of fish - Zhicheng Li; Jingyu Zhuang; Jiaming Chen; Jizhen Cao; Qing Han; Zhi Luo; Baotun Wang; Hebing Wang; Anxing Li (Journal of Fish Diseases, 2024)
Amyloodinium ocellatum is among the most devastating protozoan parasites, causing huge economic losses in the mariculture industry. However, the pathogenesis of amyloodiniosis remains unknown, hindering the development of targeted anti‐parasitic drugs. The A. ocellatum in vitro model is an indispensable tool for investigating the pathogenic mechanism of amyloodiniosis at the cellular and molecular levels. The present work developed a new cell line, ALG, from the gill of yellowfin seabream ( Acanthopagrus latus ). The cell line was routinely cultured at 28°C in Dulbecco's modified Eagle medium (DMEM) supplemented with 15% fetal bovine serum (FBS). ALG cells were adherent and exhibited an epithelioid morphology; the cells were stably passed over 30 generations and successfully cryopreserved. The cell line derived from A. latus was identified based on partial sequence amplification and sequencing of cytochrome B ( Cyt b ). The ALG was seeded onto transwell inserts and found to be a platform for in vitro infection of A. ocellatum , with a 37.23 ± 5.75% infection rate. Furthermore, scanning electron microscopy (SEM) revealed that A. ocellatum parasitizes cell monolayers via rhizoids. A. ocellatum infection increased the expression of apoptosis and inflammation‐related genes, including caspase 3 ( Casp 3 ), interleukin 1 ( IL‐1 ), interleukin 10 ( IL‐10 ), tumour necrosis factor‐alpha ( TNF‐α ), in vivo or in vitro. These results demonstrated that the in vitro gill cell monolayer successfully recapitulated in vivo A. latus host responses to A. ocellatum infection. The ALG cell line holds great promise as a valuable tool for investigating parasite–host interactions in vitro.

Polystyrene microplastics with absorbed nonylphenol induce intestinal dysfunction in human Caco-2 cells - Fangfang Ding; Huimei Wang; Yingzhi Li; Xueping Leng; Jiaming Gao; Danfei Huang (Environmental Toxicology and Pharmacology, 2024)

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Hyporheic exchange in a compound channel under unsteady flow: Numerical simulations - Jiaming Liu; Yang Xiao; Pei Xin; Nairu Wang; Saiyu Yuan; Taotao Zhang; Chentao Li; Carlo Gualtieri (Journal of Hydrology, 2024)

Cavity effects on spontaneous ignition of pressurized hydrogen jets - Jiaxin Zhang; Jiaming Huang; Qingxin Ba; Bo Zhou; David M. Christopher; Ming Gao; Xuefang Li (Fuel, 2024)

Thermal inactivation kinetics of Listeria monocytogenes in milk under isothermal and dynamic conditions - Xiang Wang; Jiaming Zheng; Linyin Luo; Yi Hong; Xiaofeng Li; Yuqi Zhu; Yufan Wu; Li Bai (Food Research International, 2024)

Carbon emissions and low-carbon development in Olefin industry - Qun Shen; Jiaming Gu; Li Shang; Shuang Liu; Xuehang Song; Weisheng Yu; Yongping Liu; Nannan Sun; Wei Wei (Environmental Research, 2024)

Image-guided structure-constrained inversion of electrical resistivity data for improving contaminations characterization - Xinmin Ma; Jieyi Zhou; Jing Li; Jiaming Zhang; Chunmei Han; Lili Guo; Shupeng Li; Deqiang Mao (Computers & Geosciences, 2024)

Zinc saponite protection layer with fast zinc-ion transfer kinetics to enable highly reversible Zn anode - Jiaming Li; Hanhao Liang; Jian Wu; Jiancheng Xu; Yini Long; Jianglin Wang; Zhanhong Yang (Chemical Engineering Journal, 2024)

EEGNet-based multi-source domain filter for BCI transfer learning - Mengfan Li; Jundi Li; Zhiyong Song; Haodong Deng; Jiaming Xu; Guizhi Xu; Wenzhe Liao (Medical & Biological Engineering & Computing, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Research on anode pressure control and dynamic performance of proton-exchange membrane fuel cell system for vehicular application - Heng Wei; Changqing Du; Xingyi Li; Chenxu Shi; Jiaming Zhang (Fuel, 2024)

Heterologous expression of protein-glutaminase in Escherichia coli Nissle 1917 for improved flavor properties of soy protein and its implications on high-moisture extrudates - Jiaming Li; Xinwen Zhang; Shijun Luo; Xinhong Wu; Guoqiang Zhang; Jianghua Li; Xiao Liu (Food Bioscience, 2024)

Biphasic solvents based on dual-functionalized ionic liquid for enhanced post-combustion CO2 capture and corrosion inhibition during the absorption process - Jiaming Mao; Chang Li; Yanbin Yun; Jia Liu; Wenjuan Yang; Meng Li; Lihua Wang; Chunli Li; Wenli Liu (Chemical Engineering Journal, 2024)

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Effectively solve the obstacle in the old residential building energy-saving renovation from the perspective of a four-party evolutionary game - Peng Wang; Haiyun Chen; Zhiyuan Si; Ling Jia; Jiaming Wang; Keying Li; Chenglong Wang (Environmental Science and Pollution Research, 2024)

High-efficient photocatalytic degradation of multiple pollutants by CdPS3 nanosheets - Bingda Li; Jiaming Song; Yuting Li; Chaoying Meng; Shuxian Wang; Linghao Zong; Honggang Ye; Yishuai Jing; Feng Teng; Peng Hu; Haibo Fan; Guangde Chen; et al. (Process Safety and Environmental Protection, 2024)

Kinetic modeling and mechanisms of parahalogenated phenols degradation by UV222/H2O2 - Min Zhao; Ting Li; Yizhan Zhang; Jiaming Gan; Yiting Zhao; Xin Yu; Lei Wang (Journal of Cleaner Production, 2024)

Rheological and tribological properties of high internal phase emulsions stabilized by pH-induced soy protein isolate-carrageenan complex coacervates - Fanjun Meng; Jiaming Li; Cong Yang; Miao Wang; Xiao Liu (Food Hydrocolloids, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

An image-based system for locating pruning points in apple trees using instance segmentation and RGB-D images - Siyuan Tong; Jiaming Zhang; Wenbin Li; Yaxiong Wang; Feng Kang (Biosystems Engineering, 2023)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Polygons with halite-crusted floors and gypsum-raised rims in western Qaidam Basin and implications for polygonal landforms on Mars - Jiaming Zhu; Bo Wu; Tianlei Zhao; Yiliang Li (Geomorphology, 2023)

Regional Modeling of the Lithospheric Magnetic Field from Local and Satellite Constraints: A Case Study of the Xinjiang Region - Yan Feng; Jiaxuan Zhang; Shengqing Xiong; JinYuan Zhang; Jiaming Ou; Shuang Liu; Yijun Li; Ya Huang (Pure and Applied Geophysics, 2023)

Investigation of Mechanical Properties of Quartz and Illite in Shale Using Molecular Dynamics Simulation - Shuang Liang; Mingyu Gao; Shuo Sun; Yikun Liu; Wanxin Li; Jingkun Wang; Jiaming Wang; Chengfeng Yin (Natural Resources Research, 2023)

Non-uniform milling caused by preferential orientation of rice grains in friction rice mills - Jiaming Fei; Wenyu Feng; Shaohang Shen; Yanlong Han; Anqi Li; Xianzhi Hao; Fuguo Jia; Ze Sun; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2023)

Microseismic monitoring and experimental study on rockburst in water-rich area of tunnel - Shibin Tang; Jiaming Li; Liexian Tang; Leitao Zhang (Tunnelling and Underground Space Technology, 2023)

Revealing the spatio-temporal characteristics and impact mechanism of carbon emission in China's urban agglomerations - Ziyi Wang; Jingxiang Zhang; Pingjia Luo; Dongqi Sun; Jiaming Li (Urban Climate, 2023)

Insights into chloride sorption and phase transformation of the synthesized Ca-Al bimetallic oxides in flue gas desulfurization wastewater - Zhen Zhou; Qiaoling Zhu; Ziwei Lan; Yuyue Yang; Li Zeng; Chengrui Liu; Jiaming Guo; Xiaodan Zhao (Chemical Engineering Journal, 2023)

Analysis of variation characteristics, transport paths, and influencing factors of atmospheric NO2 pollution in Western Europe - Jiaming Zhang; Tianzhen Ju; Bingnan Li; Chunxue Li; Jinyang Wang; Xuhui Xia; Xiaowen Niu (Environmental Monitoring and Assessment, 2023)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Discrete solutions and interaction dynamics for coupled nonlocal discrete nonlinear Schrödinger equations in an inhomogeneous optical fiber - Li Li; Fajun Yu; Jiaming Yu (Wave Motion, 2023)

Statistical modeling and dependence analysis for tide level via multivariate extreme value distribution method - Ali Tian; Xufeng Shu; Jiaming Guo; Haoyun Li; Renchuan Ye; Peng Ren (Ocean Engineering, 2023)

Seismic response analysis of submerged floating tunnel considering non-uniform excitation and flexible-support boundary effect - Jiaming Xie; Jing Li; Jianyun Chen; Qiang Xu (Ocean Engineering, 2023)

Mechanical and internal structural damage evolution in cold recycled mixture under fatigue loading - Hu Yang; Liyan Shan; Lingwen Li; Zhiwei Li; Jiaming Yan (Journal of Cleaner Production, 2023)

Ingestion preference and efficiencies of different polymerization types foam plastics by Tenebrio molitor larvae, associated with changes of both core gut bacterial and fungal microbiomes - Yijing Wang; Xin Zhao; Jiaming Wang; Yue Weng; Yumeng Wang; Xin Li; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2023)

Zwitterionic loose polyamide nanofiltration membrane with good antifouling properties for efficient removal of humic acid and dyes - Chengbao Geng; Fangbo Zhao; Hongyan Niu; Jiaming Zhang; Yang Liu; Lijia Liu; Hongxing Dong; Zhiguo Li; Hongxu Chen (Journal of Environmental Chemical Engineering, 2023)

Catalytic degradation of bisphenol a (BPA) in water by immobilizing silver-loaded graphene oxide (GO-Ag) in ultrafiltration membrane with finger-like structure - Ye Yang; Fangbo Zhao; Liu Yang; Jiaming Zhang; Hee-Deung Park; Zhiguo Li; Hongxu Chen; Ximeng Zhang; Mingjin Gao (Chemical Engineering Journal, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Spatial and temporal distribution of absorbing aerosols in sub-Saharan Africa and GTWR model analysis - Chunxue Li; Tianzhen Ju; Bingnan Li; Jiaming Zhang; Jinyang Wang; Xuhui Xia; Shengtong Lei (Air Quality, Atmosphere & Health, 2023)

Recent advances in sulfidized nanoscale zero-valent iron materials for environmental remediation and challenges - Wenjing Xue; Jun Li; Xinyu Chen; Hongdou Liu; Siqi Wen; Xiaoyu Shi; Jiaming Guo; Yang Gao; Jian Xu; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Tectonomagmatic setting and magmatic Cu-PGE metallogeny during the late Neoproterozoic in the Eastern Kunlun Orogen, NW China: Insights from the Hatu Cu-Pt-Pd-bearing mafic-ultramafic intrusion - Liang Li; Fengyue Sun; Li Wang; Yajing Zhang; Chao Wang; Ye Qian; Tuofei Zhao; Jiaming Yan; Shucheng Tan (Precambrian Research, 2023)

Influence of hemin on structure and emulsifying properties of soybean protein isolate - Jiaming Zhang; Yangyang Jia; Wenjin Wu; Yingying Zhang; Ping Chen; Xiaofang Li; Xuetuan Wei; Chunmei Li; Kaikai Li (Food Chemistry, 2023)

Analysis of Remote Sensing Monitoring of Atmospheric Ozone in Japan from 2010 to 2021 - Shengtong Lei; Tianzhen Ju; Bingnan Li; Xuhui Xia; Cheng Huang; Jiaming Zhang; Chunxue Li (Water, Air, & Soil Pollution, 2023)

An interval-valued carbon price forecasting method based on web search data and social media sentiment - Jinpei Liu; Xue Li; Piao Wang; Huayou Chen; Jiaming Zhu (Environmental Science and Pollution Research, 2023)

Degradation and dechlorination of trichloroacetic acid induced by an in situ 222 nm KrCl* excimer radiation - Jiaming Gan; Ting Zhu; Yizhan Zhang; Dailin Li; Ting Li; Min Zhao; ZengXia Zhao; Lei Wang (Chemosphere, 2023)

Numerical investigation of flow similarity of rice grains in friction rice mill and establishment of scale-up rule - Anqi Li; Fuguo Jia; Jiaming Fei; Yanlong Han; Peiyu Chen; Wenyu Feng; Xianzhi Hao; Shaohang Shen; Hao Li (Computers and Electronics in Agriculture, 2023)

Fibrillation of whey protein isolate by radio frequency heating for process efficiency: Assembly behavior, structural characteristics, and in-vitro digestion - Shuangshuang Wang; Yuxia Xie; Yi Ding; Zhenquan Huo; Jiaming Li; Jiaqing Song; Yucui Huo; Lili Zhao; Jing Zhang; Shaojin Wang; Jiaying Zhang; Wupeng Ge (Innovative Food Science & Emerging Technologies, 2023)

Analysis on the Influencing Factors and Future Trend of HCHO Pollution in Brazil - Cheng Huang; Tianzhen Ju; Bingnan Li; Jinyang Wang; Jiaming Zhang; Shengtong Lei; Chunxue Li (Water, Air, & Soil Pollution, 2023)

A Real-Time Lightweight Detection Algorithm for Deck Crew and the Use of Fishing Nets Based on Improved YOLOv5s Network - Jiaming Wang; Xiangbo Yin; Guodong Li (Fishes, 2023)
A real-time monitoring system for the operational status of fishing vessels is an essential element for the modernization of the fishing industry. The operational status of fishing vessels can be identified by using onboard cameras to detect the deck crew and the use of fishing nets. Due to the typically limited processing capacity of shipboard equipment and the significant memory consumption of detection models, general target detection models are unable to perform real-time image detection to identify the operational status of fishing vessels. In this paper, we propose a lightweight real-time deck crew and the use of a fishing net detection method, YOLOv5s-SGC. It is based on the YOLOv5s model, which uses surveillance cameras to obtain video of fishing vessels operating at sea and enhances the dataset. YOLOv5s-SGC replaces the backbone of YOLOv5s with ShuffleNetV2, replaces the feature fusion network with a modified Generalized-FPN, and adds the CBAM attention module in front of the detection head.

Performance and response of coupled microbial fuel cells for enhanced anaerobic treatment of azo dye wastewater with simultaneous recovery of electrical energy - Liming Hu; Na Liu; Chang Li; Jiaming Mao; Meng Li; Yanbin Yun; Wenli Liu (Environmental Science and Pollution Research, 2023)

Four new terpenoids and other metabolites with potential anti-complementary activities from the aerial parts of Dracocephalum moldavica (Lamiaceae) - Jiaming Wang; Jinfeng Sun; Long Jin; Yanyan Huang; Mengjie Wang; Mei Jin; Shengbao Diao; Wei Zhou; Gao Li (Natural Product Research, 2023)

Magnetic field assisted process for preparing anti-biofouling PVDF membranes incorporated by hydrophilic magnetic palygorskite - Hengyang Mao; Jiayun Zhu; Shouyong Zhou; Jiaming Wang; Mengting Li; Ailian Xue; Meisheng Li; Yijiang Zhao; Wenbo Peng; Weihong Xing (Applied Clay Science, 2023)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

FOXO-like Gene Is Involved in the Regulation of 20E Pathway through mTOR in Eriocheir sinensis - Jiaming Li; Yuhan Ma; Zhichao Yang; Fengchi Wang; Jialin Li; Yusheng Jiang; Dazuo Yang; Qilin Yi; Shu Huang (Journal of Marine Science and Engineering, 2023)
The Forkhead Box O (FOXO) gene plays a key role in various biological processes, such as growth, metabolism, development, immunity and longevity. Molting is an essential process for crustacean growth, which is mainly regulated by 20-hydroxyecdysone (20E) and molt-inhibiting hormone (MIH). Although the role of FOXO in regulating the immune response of crustaceans is well documented, its involvement in controlling crustacean molting remains unclear. In this study, a FOXO-like gene (designed as EsFOXO-like) was identified in Eriocheir sinensis, and the regulation of the 20E pathway by EsFOXO-like was also investigated. The coding sequence of EsFOXO-like was 852 bp, which consisted of 283 amino acids including a conserved Forkhead (FH) domain. EsFOXO-like shared high similarity with FOXO genes from other crustaceans, and the mRNA expression levels of the EsFOXO-like gene were highest in the hepatopancreas and lowest in the hemocytes. However, transcription and protein expression of the EsFOXO-like gene were found to be up-regulated only during the pre-molt stage in the hepatopancreas, with lower expression levels observed at the post-molt stage. To explore the role of EsFOXO-like in the 20E pathway, EsFOXO-like was firstly inhibited by a specific FOXO inhibitor (AS1842856) and then through an EsFOXO-like dsRNA injection, respectively, and the results showed that the relative expression levels of EsFOXO-like were notably decreased in the hepatopancreas after both the inhibitor and dsRNA treatments. The 20E concentration, the mRNA expression levels of the 20E receptors including the ecdysone receptor (EcR) and the retinoid-X receptor (RXR) and EsmTOR transcription in the AS1842856 group or the EsFOXO-RNAi group were all significantly higher than that in the control group, while the mRNA expression level of EsMIH was significantly decreased after EsFOXO-like inhibition. To further investigate whether the EsFOXO-like acts through mTOR or not, Rapamycin was administered to inhibit mTOR activity in EsFOXO-like inhibited crabs. The results revealed a significant reduction in the concentration of 20E and the expression level of EsMIH in the AS1842856 + Rapamycin group compared to the AS1842856 + DMSO group, accompanied by an increase in EsEcR and EsRXR expression. These findings collectively suggest that EsFOXO-like regulates the 20E pathway through mTOR, which offered valuable insights into the understanding of the molting process in crustaceans.

The heterogeneity impact of factor market distortions on GTFP: from the view of resource-based cities - Jiaming Wang; Lianyong Feng; Bo Li (Environmental Science and Pollution Research, 2023)

Observation of black carbon in Northern China in winter of 2018–2020 and its implications for black carbon mitigation - Yang Wang; Qiuge Ju; Zhenyu Xing; Jiaming Zhao; Song Guo; Fuxing Li; Ke Du (Science of The Total Environment, 2023)

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

Why the same economic reform leads to different urbanization route? --The comparative study of China and India - Jiaming Li; Ziyi Wang; Mingyi Liu (Land Use Policy, 2023)

Superiority of UV222 radiation by in situ aquatic electrode KrCl excimer in disinfecting waterborne pathogens: Mechanism and efficacy - Ting Li; Yizhan Zhang; Jiaming Gan; Xin Yu; Lei Wang (Journal of Hazardous Materials, 2023)

Efficient separation and comprehensive extraction of aluminum, silicon, and iron from coal fly ash by a cascade extraction method - Xiaodan Zhao; Li Zeng; Jiaming Guo; Qiaoling Zhu; Zhuojun Huang; Lifeng Lin; Xuanang Chen; Jing Cao; Zhen Zhou (Journal of Cleaner Production, 2023)

Effects of operating conditions on supercritical methanol liquefaction of polypropylene - Binbin Fu; Litao Geng; Guangchao Jia; Zhilong Yuan; Peitao Zhao; Rongyang Zhao; Cuiping Wang; Jiaming Li (Journal of Environmental Chemical Engineering, 2023)

Study on dynamic response mechanism of rice grains in friction rice mill and scale-up approach of parameter based on discrete element method - Anqi Li; Fuguo Jia; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Xianzhi Hao; Jiaming Fei; Shaohang Shen; Wenyu Feng (Innovative Food Science & Emerging Technologies, 2023)

The role of the joint capsule in the stability of the elbow joint - Fang Wang; Hao Wang; Mingxin Li; Shuoqi Jia; Jiaming Wang; Jianguo Zhang; Yubo Fan (Medical & Biological Engineering & Computing, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

The mechanism of bran layer removal in friction rice mills - Jiaming Fei; Wenyu Feng; Fuguo Jia; Yanlong Han; Peiyu Chen; Anqi Li; Yinglong Wang; Jincheng Zhang; Shaohang Shen; Xianzhi Hao (Biosystems Engineering, 2023)

Preparation of a novel metal-free polypyrrole-red phosphorus adsorbent for efficient removal of Cr(VI) from aqueous solution - Longyu Qiu; Yingjun Wang; Rui Sui; Chenxi Zhu; Weiwei Yang; Yongsheng Yu; Jiaming Li (Environmental Research, 2023)

Improving the prediction accuracy of small-strain shear modulus of granular soils through PSD: An investigation enabled by DEM and machine learning technique - Xingyang Liu; Zhanchao Li; Degao Zou; Linsong Sun; Khailah Ebrahim Yahya; Jiaming Liang (Computers and Geotechnics, 2023)

In-depth understanding of catalytic and adsorbing effects in polysulfides conversion and rationally designing coaxial nanofibers for Li-S batteries - Jiaming Tian; Zihan Shen; Huiting Cheng; Xin Jin; Zhonghua Li; Yang Wen; Junfeng Hui; Shaohua Guo; Huigang Zhang; Qingshan Zhu (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Experimental investigation on pressure oscillation induced by steam injection into subcooled water through an opposite nozzle - Haitao Ren; Dingding Liang; Tao Lu; Jie Wang; Pei Yu; Jie Li; Jiaming Zhao; Ping Xiong (Annals of Nuclear Energy, 2023)

Correction to: Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Depth-dependent drivers of soil aggregate carbon across Tibetan alpine grasslands - Junxiao Pan; Jiawei Shi; Dashuan Tian; Ruiyang Zhang; Yang Li; Yunlong He; Lei Song; Song Wang; Yicheng He; Jiaming Yang; Chunxue Wei; Shuli Niu; et al. (Science of The Total Environment, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

MOF-derived ultrasmall Ru@RuO2 heterostructures as bifunctional and pH-universal electrocatalysts for 0.79 V asymmetric amphoteric overall water splitting - Zhe Li; Jizhao Zou; Tao Liang; Xinrui Song; Zhangjian Li; Jiaming Wen; Minggui Peng; Xierong Zeng; Haitao Huang; Hongliang Wu (Chemical Engineering Journal, 2023)

Biological hydrogen with industrial potential: Improvement and prospection in biohydrogen production - Weixian Chen; Tianpei Li; Yangyi Ren; Jiaming Wang; Hui Chen; Qiang Wang (Journal of Cleaner Production, 2023)

Design, synthesis, and biological evaluation of dual-target COX-2/5-LOX inhibitors for the treatment of inflammation - Le Du; Shuaishuai Du; Jiaming Li; Hongwei Wang (Medicinal Chemistry Research, 2023)

A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity - Jiaming Wang; Jinfeng Sun; Long Jin; Mengjie Wang; Yanyan Huang; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2023)

Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength - Yu Cao; Chengxue Ma; Jinni Yao; Wanpeng Chen; Li Gu; Hongxia Liu; Caihong Liu; Jiaming Xiong; Xiaoliu Huangfu (Chemosphere, 2023)

Breakage mechanism of brown rice grain during rubber roll hulling - Peiyu Chen; Fuguo Jia; Jincheng Zhang; Yanlong Han; Anqi Li; Yinglong Wang; Jiaming Fei; Shaohang Shen; Wenyu Feng; Xianzhi Hao (Biosystems Engineering, 2023)

Automatic arrival-time picking of P- and S-waves of microseismic events based on object detection and CNN - Jiaming Li; Kunyao Li; Shibin Tang (Soil Dynamics and Earthquake Engineering, 2023)

Histone deacetylase CsHDA6 mediates the regulated formation of the anti-insect metabolite α-farnesene in tea (Camellia sinensis) - Shuhua Wu; Yuhua Yang; Jiaming Chen; Jianlong Li; Guotai Jian; Jie Yang; Kaiquan Mao; Lanting Zeng; Dachuan Gu (Plant Science, 2023)

Tentative exploration on water-promoted catalytic ozonation of Cl-VOCs and feasibility of application in complex flue gas over monolithic cobalt catalyst - Li Xiang; Luyang Zhang; Jiaming Shao; Fawei Lin; Zhihua Wang; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

Fracture behavior investigation of self-compacting rubberized concrete by DIC and mesoscale modeling - Xing Li; Fuheng Ma; Xudong Chen; Jiang Hu; Jiaming Wang (Journal of Cleaner Production, 2023)

Numerical simulation approach for predicting rice milling performance under different convex rib helix angle based on discrete element method - Anqi Li; Fuguo Jia; Shaohang Shen; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Wenyu Feng; Jiaming Fei; Xianzhi Hao (Innovative Food Science & Emerging Technologies, 2023)

Energy management of the grid-connected residential photovoltaic-battery system using model predictive control coupled with dynamic programming - Bin Zou; Jinqing Peng; Rongxin Yin; Zhengyi Luo; Jiaming Song; Tao Ma; Sihui Li; Hongxing Yang (Energy and Buildings, 2023)

In-situ construction of BiOBr/Bi2WO6 S-scheme heterojunction nanoflowers for highly efficient CO2 photoreduction: Regulation of morphology and surface oxygen vacancy - Jiaming Wu; Keyan Li; Siyu Yang; Chunshan Song; Xinwen Guo (Chemical Engineering Journal, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

The Impact of Scour on Laterally Loaded Piles Bored and Socketed in Marine Clay - Chentao Li; Yang Xiao; Jieqing Liu; Qingwei Lin; Taotao Zhang; Jiaming Liu (Journal of Marine Science and Engineering, 2022)
The majority of long-span bridges and offshore construction in deep water are supported by bored pile foundations. Pile foundations under water will be susceptible to scour, which will pose a significant danger to their safe operation. A three-dimensional finite element (FE) numerical analysis was conducted to examine the influence of scour on the responses of laterally loaded drilled piles in marine clays. First, the FE numerical model was calibrated using field test data of a drilled pile that did not include scour in soft marine clay. The findings of numerical modeling reveal that scour decreases the ultimate lateral capacity of socketed drilled piles, with the percentage of reduction being strongly related to scour types and depth, but moderately related to scour hole width and slope angle. Finally, a semi-empirical formula for calculating the effects of scour on the lateral capacity of socketed drilled piles following scour is presented. This method may be utilized fast and effectively to calculate scour’s effects.

The influence of water-stress loading sequences on the creep behavior of granite - Shibin Tang; Jiaming Li; Shun Ding; Leitao Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Lack of Knowledge, the main Stumbling Block of Fertility Preservation Promotion in China - Meng Wang; Lixia Zhu; Hua Xiong; Jiaming Wang; Zhou Li; Liu Yang; Lei Jin; Qingsong Xi (Journal of Cancer Education, 2022)

Scientific attributes and expression methods of geographical boundary - Guoan Tang; Jilong Li; Liyang Xiong; Jiaming Na (Journal of Geographical Sciences, 2022)

Design, synthesis and biological evaluation of indoline derivatives as multifunctional agents for the treatment of ischemic stroke - Shuaishuai Du; Fan Jin; Jiaming Li; Xiaodong Ma; Hongwei Wang; Shihu Qian (Medicinal Chemistry Research, 2022)

Characteristics of a rapid landsliding area along Jinsha River revealed by multi-temporal remote sensing and its risks to Sichuan-Tibet railway - Jiaming Yao; Hengxing Lan; Langping Li; Yiming Cao; Yuming Wu; Yixing Zhang; Chaodong Zhou (Landslides, 2022)

Genome-wide genetic diversity and IBD analysis reveals historic dissemination routes of pear in China - Xuening Chen; Mingyue Zhang; Manyi Sun; Yueyuan Liu; Shengnan Li; Bobo Song; Mengyan Li; Shaoling Zhang; Runze Wang; Jiaming Li; Kejiao Zhao; Jun Wu (Tree Genetics & Genomes, 2022)

Phosphorylation of CRMP2 by Cdk5 Negatively Regulates the Surface Delivery and Synaptic Function of AMPA Receptors - Longfei Cheng; Keen Chen; Jiong Li; Jiaming Wu; Jiaqi Zhang; Li Chen; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2022)

NoiD, a DedA membrane protein required for homeostasis maintaining of Rhizobium leguminosarum biovar viciae during symbiosis with Pisum sativum - Xiaofang Li; Jiaming Xu; Yajuan Wei; Zirui Chen (Symbiosis, 2022)

Two new phenolic glycosides with anti-complementary activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Chao Ye; Jiaming Wang; Long Jin; Ying Jie Ma; Wei Zhou; Gao Li (Natural Product Research, 2021)

Diverse transcriptional patterns of homoeologous recombinant transcripts in triploid fish (Cyprinidae) - Li Ren; Xueyin Zhang; Jiaming Li; Xiaojing Yan; Xin Gao; Jialin Cui; Chenchen Tang; Shaojun Liu (Science China Life Sciences, 2021)

Numerical Simulation of Depth Tracking Control of an Underwater Towed System Coupled with Wave–Ship Interference - Xianyuan Yang; Jiaming Wu; Quanlin Li; Haiyan Lv (Journal of Marine Science and Engineering, 2021)
This paper presents a numerical study of the depth tracking control for an underwater towed system under wave–ship interference condition. To overcome the laminations of ignoring the hydrodynamic factors and wave–ship interference in the existing simulation model for the depth tracking operation of the underwater towed system, a numerical model combining the control system with the computational fluid dynamics (CFD) method based on the overset mesh technique is explored and constructed; the influence of towing ship and head waves is introduced into the numerical analysis of the underwater towed system; a depth control system based on the center of gravity adjustment is proposed and its control characteristics are discussed. The fluid motion around the towed vehicle and the towing ship is governed by the Navier–Stokes equations, and the overset mesh technique is applied for the numerical solution of the equations. The towing cable connecting the towed vehicle and towing ship is governed by the quasi-steady-state catenary equations. The depth tracking controller adjusting the longitudinal position of a shifting weight is constructed based on the proportional–integral–derivative (PID) algorithm. The simulation results show that the numerical simulation system is practicable, and the depth tracking control system is feasible, effective, and robust.

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

Gene polymorphism of chalcone isomerase influence the accumulation of flavonoids in licorice (Glycyrrhiza spp.) - Xiaodong Zhang; Shaokai Tian; Lin Qi; Wendong Li; Jiaming Hou; Lin Yang; Zhixin Zhang; Ying Liu (Genetic Resources and Crop Evolution, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells - Jiaming Wang; Mei Jin; Chunshi Jin; Chao Ye; Yi Zhou; Rongshen Wang; Huanhuan Cui; Wei Zhou; Gao Li (Natural Product Research, 2020)

A novel facial attractiveness evaluation system based on face shape, facial structure features and skin - Jian Zhao; Miao Zhang; Chen He; Xie Xie; Jiaming Li (Cognitive Neurodynamics, 2020)

Development and characterization of 33 SNP markers for the red-crowned crane (Grus japonensis) using a genotyping-by-sequencing approach - Nan Xu; Yining Chen; Jiaming Zhang; Qingzheng Zhang; Jing Yang; Jingjing Li; Hongyi Liu (Conservation Genetics Resources, 2020)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

A conjugated mTOR/MEK bifunctional inhibitor as potential polypharmacological anticancer agent: the prototype compound discovery - Qiangqiang Tao; Fang Fang; Jiaming Li; Yong Wang; Can Zhao; Jingtai Liang; Xiaodong Ma; Hao Wang (Medicinal Chemistry Research, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

Important progress and future prospects for studies on urban public recreational space in China - Ling Yu; Jiaming Liu; Tao Li (Journal of Geographical Sciences, 2019)

Analysis of deformation characteristics for a reservoir landslide before and after impoundment by multiple D-InSAR observations at Jinshajiang River, China - Lingjing Li; Xin Yao; Jiaming Yao; Zhenkai Zhou; Xin Feng; Xinghong Liu (Natural Hazards, 2019)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Identification and classification of resource-based cities in China - Jianhui Yu; Jiaming Li; Wenzhong Zhang (Journal of Geographical Sciences, 2019)

Geochronology, Geochemistry, and Hf Isotopic Compositions of Monzogranites and Mafic-Ultramafic Complexes in the Maxingdawannan Area, Eastern Kunlun Orogen, Western China: Implications for Magma Sources, Geodynamic Setting, and Petrogenesis - Jiaming Yan; Guosheng Sun; Fengyue Sun; Liang Li; Haoran Li; Zhenhua Gao; Lei Hua; Zhengping Yan (Journal of Earth Science, 2019)

Study of mosaicism of Pyropia yezoensis - Yuan He; Wei Zhou; Jiaming Li; Songdong Shen (Marine Biology Research, 2019)

Comparative morphology of in vivo and in vitro laticiferous cells and potential use of in vitro laticifers in early selection of rubber tree clones - Deguan Tan; Anuwat Kumpeangkeaw; Xuepiao Sun; Weiguo Li; Yiming Zhu; Jiaming Zhang (Trees, 2019)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

International symposiums on urbanization and planning in China and India, organized by the delegation of the Geographical Society of China - Yu Yang; Jiaming Li (Journal of Geographical Sciences, 2017)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)

Small RNA changes in synthetic Brassica napus - Ying Fu; Meili Xiao; Huasheng Yu; Annaliese S. Mason; Jiaming Yin; Jiana Li; Dongqing Zhang; Donghui Fu (Planta, 2016)

Chemical and isotopic constrains on the origin of brine and saline groundwater in Hetao plain, Inner Mongolia - Jun Liu; Zongyu Chen; Lijuan Wang; Yilong Zhang; Zhenghong Li; Jiaming Xu; Yurong Peng (Environmental Science and Pollution Research, 2016)

Soil heavy metal contamination related to roasted stone coal slag: a study based on geostatistical and multivariate analyses - De’an Li; Jianguo Jiang; Tianran Li; Jiaming Wang (Environmental Science and Pollution Research, 2016)

Stacking S5-n and f5-n to overcome sterility in indica–japonica hybrid rice - Jiaming Mi; Guangwei Li; Jianyan Huang; Huihui Yu; Fasong Zhou; Qifa Zhang; Yidan Ouyang; Tongmin Mou (Theoretical and Applied Genetics, 2016)

Removal of Pb and Zn from contaminated soil by different washing methods: the influence of reagents and ultrasound - Jiaming Wang; Jianguo Jiang; Dean Li; Tianran Li; Kaimin Li; Sicong Tian (Environmental Science and Pollution Research, 2015)

Industrial spatial agglomeration using distance-based approach in Beijing, China - Jiaming Li; Wenzhong Zhang; Jianhui Yu; Hongxia Chen (Chinese Geographical Science, 2015)

Study on the synergy between intra-urban resident’s migration and job change in Beijing - Jianhui Yu; Guanpeng Dong; Wenzhong Zhang; Jiaming Li (Journal of Geographical Sciences, 2015)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)

A Highly Sensitive Solid Substrate Room Temperature Phosphorimetry for Carbaryl Detection Based on its Activating Effect on NaIO4 Oxidizing Fluorescein - Jiaming Liu; Qitong Huang; Zhen-bo Liu; Xiaofeng Lin; Li-Hong Zhang; Chang-Qing Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2014)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)

Extensive tRNA Gene Changes in Synthetic Brassica napus - Lijuan Wei; Zeshan An; Annaliese S. Mason; Meili Xiao; Ying Guo; Jiaming Yin; Jiana Li; Donghui Fu (Journal of Molecular Evolution, 2014)

Characterization of transcriptional activation and inserted-into-gene preference of various transposable elements in the Brassica species - Caihua Gao; Meili Xiao; Lingyan Jiang; Jiana Li; Jiaming Yin; Xiaodong Ren; Wei Qian; Ortegón Oscar; Donghui Fu; Zhanglin Tang (Molecular Biology Reports, 2012)

Production of cyclic adenosine monophosphate by Arthrobacter sp. A302 using fed-batch fermentation with pH-shift control - Jiaming Cao; Xiaochun Chen; Huajing Ren; Jindan Zhang; Lei Li; Yong Chen; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2012)

Dynamic mathematical models of batch experiments and fed-batch cultures for cyclic adenosine monophosphate production by Arthrobacter A302 - Lei Li; Xiaochun Chen; Huajing Ren; Jiaming Cao; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2011)

The Arg194Trp polymorphism in the XRCC1 gene and cancer risk in Chinese Mainland population: a meta-analysis - Jin Huang; Jie Zhang; Yuliang Zhao; Banghua Liao; Jiaming Liu; Ling Li; Mingheng Liao; Lanlan Wang (Molecular Biology Reports, 2011)

Characterization and comparison of gene-based simple sequence repeats across Brassica species - Caihua Gao; Zhanglin Tang; Jiaming Yin; Zeshan An; Donghui Fu; Jiana Li (Molecular Genetics and Genomics, 2011)

Contribution of the IBD5 locus to inflammatory bowel disease: a meta-analysis - Jian Wang; Xi Wang; Hong Yang; Dong Wu; Li Wang; Jiaming Qian (Human Genetics, 2011)

Isolation and characterization of a novel EAR-motif-containing gene GmERF4 from soybean (Glycine max L.) - Gaiyun Zhang; Ming Chen; Xueping Chen; Zhaoshi Xu; Liancheng Li; Jiaming Guo; Youzhi Ma (Molecular Biology Reports, 2010)

Comparative analysis of distinct non-coding characteristics potentially contributing to the divergence of human tissue-specific genes - Qianli Huang; Jiaming Guo; Qq Ge; Jesse Li-Ling; Xueping Chen; Fei Ma (Genetica, 2009)